A new rhamphorhynchid (Pterosauria: Rhamphorhynchidae) from the Middle/Upper Jurassic of Qinglong, Hebei Province, China - Lü, Junchang; Unwin, David M.; Zhao, Bo; Gao, Chunling; Shen, Caizhi (Zootaxa, 2012)
A heavily compressed, but nearly complete fossil skeleton recovered from the Middle/Upper Jurassic Tiaojishan Forma-tion of Mutoudeng, Qinglong County, Hebei Province, China, represents a new genus and species of long-tailed pterosaur,Qinglongopterus guoi gen. et sp. nov. The holotype and only known specimen has an estimated forelimb length of 0.18m. The new taxon is distinguished by a relatively short skull, a remarkably short pteroid with a distinctive knob-like distalexpansion, and a prepubis with a relatively slender distal process. Phylogenetic analysis demonstrates that Qinglongopter-us is a member of Rhamphorhynchidae, exhibiting many of the unique character states found in members of this clade.Qinglongopterus is strikingly similar to Rhamphorhynchus and more closely related to this taxon than to any other rham-phorhynchine, this pairing is supported by morphometric data and several synapomorphies (short, broad nasal process ofthe maxilla; forelimb length more than four times that of the hind limb; wing-phalanx one more than twice the length ofthe tibia). Qinglongopterus demonstrates that the highly derived skeletal morphology of Rhamphorhynchus, known onlyfrom the latest Jurassic (Tithonian) of Europe, had already appeared by the start of the Late Jurassic. This hints at evolu-tionary stasis in Rhamphorhynchinae, a phenomenon seemingly also present in two other clades of basal pterosaurs,Anurognathidae and Scaphognathinae, and contrasting sharply with basal monofenestratans which appear to have undergone extensive evolutionary change during the same interval.